2004
DOI: 10.1097/00005537-200410000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Pneumonia With an Electronic Nose: Correlation of Vapor Signature With Chest Computed Tomography Scan Findings

Abstract: The electronic nose is a new technology that continues to show promise as a potential diagnostic adjunct in the diagnosis of pneumonia and other infectious diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
71
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 18 publications
(21 reference statements)
4
71
0
Order By: Relevance
“…Our moderate results in predictive classification of TBPOS and TBNEG sputum samples are similar to previous results with other EN detectors used for infectious diseases, where breath samples instead of the headspace of sputum samples were used to attempt to identify the incidence of lung cancer, chronic obstructive pulmonary disease, asthma, and pneumonia (2,3,5,6,7,8).…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Our moderate results in predictive classification of TBPOS and TBNEG sputum samples are similar to previous results with other EN detectors used for infectious diseases, where breath samples instead of the headspace of sputum samples were used to attempt to identify the incidence of lung cancer, chronic obstructive pulmonary disease, asthma, and pneumonia (2,3,5,6,7,8).…”
supporting
confidence: 86%
“…This level of control and the randomization procedure have not been used before in other EN studies as far as we are aware. It would be of interest to know how this would influence the results from other EN reports (3,5,6,7,8).…”
mentioning
confidence: 99%
“…Diagnosis is usually based on clinical findings, chest X ray, and isolation and subsequent identification of the pathogen in culture from bronchial secretions. E-nose (Cyranose 320) analysis of exhaled breath has been shown to discriminate between patients with ventilator-associated pneumonia and healthy controls (124). Promising results have also been reported in a prospective study which showed a good correlation between breath analysis and clinical pneumonia scores (125,126).…”
Section: Other Infectionsmentioning
confidence: 95%
“…157 (4) Examples for the detection of bacterial and/or fungal respiratory disease are chronic rhinosinusitis 158 and the very promising approach to identify ventilator-associated pneumonia in patients in surgical intensive care units. [159][160][161] (5) The reason for halitosis is sulfur-containing gases of oral bacterium origin, 162 which is normally evaluated by an organoleptic test. Tanaca et al and Nonaka et al presented a clinical assessment of oral malodor by an electronic nose system.…”
Section: Disease Diagnosismentioning
confidence: 99%